2015
DOI: 10.1007/978-3-319-25485-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Author Profiling and Plagiarism Detection

Abstract: In this paper we introduce the topics that we will cover in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The findings were supported by some studies [24], [57], [80]. Finally, considerable efforts have been applied to detecting crosslanguage plagiarism, and although some authors [2]- [6], [8]- [10], [81] have proposed or identified techniques capable of detecting.…”
Section: B Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The findings were supported by some studies [24], [57], [80]. Finally, considerable efforts have been applied to detecting crosslanguage plagiarism, and although some authors [2]- [6], [8]- [10], [81] have proposed or identified techniques capable of detecting.…”
Section: B Discussionmentioning
confidence: 57%
“…Further, Franco-Salvador et al [5] examined the contributions of knowledge graphs to cross-language plagiarism detection in three areas: word meaning disambiguation, vocabulary extension, and representation through similarities to a collection of ideas; Ferrero et al [6] studied cross-language plagiarism detection techniques across six language pairings and two granularities of text units in order to reach solid findings of the best algorithms while also doing in-depth analyses of connections across document types and languages; and Tlitova et al [7]. reviewed the available techniques for detecting cross-language plagiarism in scientific publications, with a particular emphasis on the Russian-English language pair These studies attempted to provide quality information that can assist in the detection process [2], [3], [8]- [10]. Despite the authors' best efforts and different evidence-based recommendations for cross-language plagiarism detection, their implementation remains difficult due mostly to the differences in linguistic structures across languages.…”
Section: Introductionmentioning
confidence: 99%
“…The native language recognition problem touches upon various text classification tasks, such as author profiling [ 7 ], authorship attribution [ 8 ], programmer identification [ 9 ], review classification [ 10 ], and Twitter sentiment analysis [ 11 ].…”
Section: Related Workmentioning
confidence: 99%